2018
DOI: 10.1136/archdischild-2018-314924
|View full text |Cite
|
Sign up to set email alerts
|

Restricted fluid bolus volume in early septic shock: results of the Fluids in Shock pilot trial

Abstract: ObjectiveTo determine the feasibility of Fluids in Shock, a randomised controlled trial (RCT) of restricted fluid bolus volume (10 mL/kg) versus recommended practice (20 mL/kg).DesignNine-month pilot RCT with embedded mixed-method perspectives study.Setting13 hospitals in England.PatientsChildren presenting to emergency departments with suspected infection and shock after 20 mL/kg fluid.InterventionsPatients were randomly allocated (1:1) to further 10 or 20 mL/kg fluid boluses every 15 min for up to 4 hours if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 34 publications
4
52
0
1
Order By: Relevance
“…These criteria set an appropriately high bar and, thus, EFIC studies have been uncommon to date in children. However, several EFIC‐based studies have been successfully carried out in the United States and, using a related ethical design, in Europe, Canada, and Australia . For this study of two efficacious resuscitation fluids, enrollment with EFIC was approved by our IRB, endorsed by the FDA through our IND application, and proved acceptable to patients/families and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria set an appropriately high bar and, thus, EFIC studies have been uncommon to date in children. However, several EFIC‐based studies have been successfully carried out in the United States and, using a related ethical design, in Europe, Canada, and Australia . For this study of two efficacious resuscitation fluids, enrollment with EFIC was approved by our IRB, endorsed by the FDA through our IND application, and proved acceptable to patients/families and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…A mixed-methods design involving interviews and focus groups, incorporating a voting system to enable the collection of both qualitative and quantitative data. Our previous research, relevant literature and prestudy patient and public involvement guided the development of the topic guides and participant information [27][28][29]. We explored parent and practitioner views on the acceptability of the proposed GASTRIC trial including: acceptability of measuring or not measuring GRV, willingness to participate in a future trial, trial information materials, barriers and facilitators to trial recruitment (S1, example Topic guild questions).…”
Section: Methodsmentioning
confidence: 99%
“…2 The wider relevance of these findings has been hotly debated. 2 The Fluids in Shock study is an English pilot study 3 ; it randomised 75 children presenting to emergency departments with clinical sepsis and shock persisting after a fluid bolus of 20 mL/kg, to further fluid boluses of either 10 or 20 mL/kg every 15 min for up to 4 h if still shocked. 3 Participants were not as unwell as expected, there were no deaths and the authors concluded a larger UK trial was not feasible.…”
Section: Fluid Resuscitation In Early Septic Shockmentioning
confidence: 99%
“…2 The Fluids in Shock study is an English pilot study 3 ; it randomised 75 children presenting to emergency departments with clinical sepsis and shock persisting after a fluid bolus of 20 mL/kg, to further fluid boluses of either 10 or 20 mL/kg every 15 min for up to 4 h if still shocked. 3 Participants were not as unwell as expected, there were no deaths and the authors concluded a larger UK trial was not feasible. However, an accompanying editorial 2 points out that the lower dose of 10 mL/kg compared with 20 mL/kg was associated with a paediatric intensive care unit admission rate of 26 versus 32%, median paediatric intensive care unit stay of 45 h (interquartile range 18-143) versus 119 h (interquartile range 52-228), mechanical ventilation 11 versus 25% and use of inotropes 2.8 versus 15.6%, and argues, after an initial 20 mL/kg bolus, for a more conservative guideline of giving 10 mL/kg every 15 min.…”
Section: Fluid Resuscitation In Early Septic Shockmentioning
confidence: 99%